Falling through the net : socio-economic insecurity in Malaysia / Mary Magdaline Pereira - Pereira, Mary Magdaline (Universiti Teknologi MARA, Shah Alam, 2004)
Before the economic meltdown in the late 1990s, Malaysia was seen as an 'emerging tiger', one of the 'East Asian miracles'. Annual growth rate was at an amazing 9% with full employment and poverty rates fell to as low as approximately 7%. In terms of the social protection system, Malaysia outranked most of her neighbours in the Southeast Asian region. But there is more to development and economic activity than just increased efficiency of resource allocation and the accumulation of capital.